Fanon for beginners - Wyrick, Deborah Baker (Orient Blackswan Private Limited, 2000)
Philosopher, psychoanalyst, politician, propagandist, prophet...although difficult to categorize, Frantz Fanon (1925 1961) is one of the most important thinkers of the 20th century and one of our most powerful writers on race and revolution. uring his short lifetime, Fanon accomplished a great deal, including writing books that have sold millions of copies throughout the world and continue to have a profound impact on contemporary cultural debate. Fanon For Beginners concludes by examining Fanon’s influence on political practice, such as the Black Power Movement in the United States, on literary theory, and on political studies.